The limits of disenchantment : essays on contemporary European philosophy - Dews, Peter (Verso, 1995)
In this book Peter Dews explores some of the most urgent problems confronting contemporary European thought: the status of the subject after postmodernism, the ethical and existential dimensions of Critical Theory, the encounter between psychoanalysis and philosophy, and the possibilities of a non-foundational metaphysical thinking. Peters Dews's approach cuts across the hostile boundaries which usually separate different theoretical traditions. Lacan and the Frankfurt School are brought into dialogue, as are deconstruction and Ricoeur's hermeneutics. Current questions of language, communication and critique are located in a broader context, as the author ranges back over the history of modern philosophy, from poststructuralism - via Nietzsche - to German Romanticism and Idealism. A wide variety of issues is discussed in the book, including Habermas's views on the ethics of nature, Lacan's theory of Oedipal crisis, the relation between writing and the lifeworld of Derrida, and Schelling's philosophy of the 'Ages of the World'. The volume is also enlivened by forceful critiques of a range of currently influential thinkers, including Michel Foucault, Richard Rorty, Rodolphe Gasche and Slavoj Zizek.